Factors Associated With Chronic Lack of Energy In Pregnant Women - Nurdika Parsya; Asnidar; Haerani (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2021)
According to who (world health organization) the incidence of malnutrition in pregnant women ranges from 20-48% maternal mortality (AKI) in central Java during 2012 reached 678 (5.6%) cases, tending to increase compared to the previous year. In 2011 the number of AKI was recorded at 668 (5.5%) cases from 592,000 pregnant women, while in 2012 the number of AKI increased to 678 (5.6%) cases from 604,000 pregnant women. The purpose of this study was to find out the factors associated with the incidence of chronic energy deprivation (KEK) in pregnant women in the working area of Ponre Health Center of Bulukumba Regency in 2020. The research method used is quantitative research where this research uses research design with cross design sectional study. The results showed that there was a relationship between knowledge levels and income levels with the incidence of chronic energy deprivation (KEK) in pregnant women in Ponre Health Center of Bulukumba Regency, but there was no relationship between paritas or the number of pregnancies and the incidence of chronic less energy (KEK). Based on the results of research that has been done, taking into account the limitations that exist is expected for future research to improve these things and expand the sample of research not only focusing on pregnant women researchers can also examine adolescents and also partus mothers who experience chronic lack of energy (KEK).